Developmental effect of RASopathy mutations on neuronal network activity on a chip - Weiss, Eva-Maria; Guhathakurta, Debarpan; Petrušková, Aneta; Hundrup, Verena; Zenker, Martin; Fejtová, Anna (Frontiers in Cellular Neuroscience, 2024)
RASopathies are a group of genetic disorders caused by mutations in genes encoding components and regulators of the RAS/MAPK signaling pathway, resulting in overactivation of signaling. RASopathy patients exhibit distinctive facial features, cardiopathies, growth and skeletal abnormalities, and varying degrees of neurocognitive impairments including neurodevelopmental delay, intellectual disabilities, or attention deficits. At present, it is unclear how RASopathy mutations cause neurocognitive impairment and what their neuron-specific cellular and network phenotypes are. Here, we investigated the effect of RASopathy mutations on the establishment and functional maturation of neuronal networks. We isolated cortical neurons from RASopathy mouse models, cultured them on multielectrode arrays and performed longitudinal recordings of spontaneous activity in developing networks as well as recordings of evoked responses in mature neurons. To facilitate the analysis of large and complex data sets resulting from long-term multielectrode recordings, we developed MATLAB-based tools for data processing, analysis, and statistical evaluation. Longitudinal analysis of spontaneous network activity revealed a convergent developmental phenotype in neurons carrying the gain-of-function Noonan syndrome-related mutations Ptpn11 D61Y and Kras V14l . The phenotype was more pronounced at the earlier time points and faded out over time, suggesting the emergence of compensatory mechanisms during network maturation.Nevertheless, persistent differences in excitatory/inhibitory balance and network excitability were observed in mature networks. This study improves the understanding of the complex relationship between genetic mutations and clinical manifestations in RASopathies by adding insights into functional network processes as an additional piece of the puzzle.